Inside-out anal sacculectomy in small dog breeds and cats - Lee, Sang Gwan; Jeong, Seong Mok; Bae, Sunhee; Park, Yeonhee; Moon, Changhwan; Kim, Hee Young (Frontiers in Veterinary Science, 2023)
This report describes a new, simple and rapid surgical technique for the removal of anal sac in small dogs and cats. The anal sacs were simply everted using mosquito hemostatic forceps and excised with the aid of an electrocautery surgical unit. On the evaluation of postoperative complications, only one dog of 28 animals experienced short-term minor complications of mild fecal incontinence and scooting. Thus, we suggest that this new surgical technique is easy, inexpensive and time-saving and some of the complications with previously reported methods used for small dog breeds and cats may be avoided by using this technique.